Psychological Strategies for Maintaining Mental Health During the Coronavirus 2019 Pandemic - Sarraf-Razavi, Mahdiyeh; Tabatabaei, Seyyed Mohammad; Eslamzadeh, Mahboubeh; Moradi, Marjan; Feyzi, Zhaleh; Talaei, Ali; Fayyazi Bordbar, Mohammad Reza (Galen Medical Journal, 2021)
The infection caused by the novel coronavirus (COVID-19) started from China and spread out to the whole world, and became a pandemic as the world health organization declared. COVID-19 has caused many challenges in all aspects of life, including mental health for the entire human beings. The current study has reviewed some important strategies based on individual care and social support. Maintaining healthy lifestyle and doing regular life activities such as enough sleeping, doing art, listening to music, doing yoga, and meditation could be practical for individual care. Some social support strategies may include talking to trusty people or counselors to share emotions, keeping in touch with family, friends, and colleagues, supporting people via calls and texts warmly, and taking care of the elderly, children, and especially medical workers. [GMJ.2021;10:e2008]